Spatiotemporal properties of the action potential propagation in the mouse visual cortical slice analyzed by calcium imaging. - Makoto Osanai (Public Library of Science (PLoS), 2010)
The calcium ion (Ca(2+)) is an important messenger for signal transduction, and the intracellular Ca(2+) concentration ([Ca(2+)](i)) changes in response to an excitation of the cell. To reveal the spatiotemporal properties of the propagation of an excitatory signal with action potentials in the primary visual cortical circuit, we conducted a Ca(2+) imaging study on slices of the mouse visual cortex. Electrical stimulation of layer 4 evoked [Ca(2+)](i) transients around the stimulus electrode. Subsequently, the high [Ca(2+)](i) region mainly propagated perpendicular to the cortical layer (vertical propagation), with horizontal propagation being restricted. When the excitatory synaptic transmission was blocked, only weak and concentric [Ca(2+)](i) transients were observed. When the action potential was blocked, the [Ca(2+)](i) transients disappeared almost completely. These results suggested that the action potential contributed to the induction of the [Ca(2+)](i) transients, and that excitatory synaptic connections were involved in the propagation of the high [Ca(2+)](i) region in the primary visual cortical circuit. To elucidate the involvement of inhibitory synaptic connections in signal propagation in the primary visual cortex, the GABA(A) receptor inhibitor bicuculline was applied. In this case, the evoked signal propagated from layer 4 to the entire field of view, and the prolonged [Ca(2+)](i) transients were observed compared with the control condition. Our results suggest that excitatory neurons are widely connected to each other over the entire primary visual cortex with recurrent synapses, and inhibitory neurons play a fundamental role in the organization of functional sub-networks by restricting the propagation of excitation signals.